Penerapan Metode Mahir Tahsin dalam Meningkatkan Fasih Membaca Al Qur’an Peserta Didik Kelas X SMA Bahrul Ulum Bontang - Aznita, Nur; Husain, Ahmadi (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This article discusses the Implementation of the Mahir Tahsin Method in Improving the Fluency of Qur’anic Reading among Grade X Students at SMA Bahrul Ulum Bontang in the 2024/2025 Academic Year. This study aims to describe: (1) the implementation of the Mahir Tahsin method in improving the fluency of Qur’anic reading among Grade X students at SMA Bahrul Ulum Bontang, and (2) the improvement in fluency of Qur’anic reading among those students. This research uses a qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The research subjects were Grade X students participating in the Tahsin program. The findings show that the implementation of the Mahir Tahsin method was carried out through several steps: (1) using talaqqi and musyafahah methods with direct practice, (2) providing individual guidance tailored to each student's characteristics, (3) utilizing relevant learning media, and (4) encouraging students to regularly read the Qur’an correctly through daily routines. Additionally, to assess the improvement in students’ fluency, teachers conducted periodic evaluations—weekly, monthly, and annually. Although some students showed slow progress, overall, the students demonstrated significant improvement in their Qur’anic reading fluency. The implementation of the Mahir Tahsin method proved to have a positive impact on students' mastery of tajwid and fluency in Qur’anic reading. The consistency of the program implementation, special attention to students experiencing difficulties, and follow-up on evaluation results were key factors in the success of this method in fostering fluent Qur’anic reading aligned with tajwid rules.